Lecteur méfiant de science-fiction et développement de savoir-faire en lecture - Philippe Clermont (ReS Futurae)
Our article aims to identify the pragmatics of science fiction texts, the way in which they are perceived and handled by readers, especially students. SF literature tends to inscribe in the text the figure of the reader-investigator, or even of the suspicious reader. While any literary reading in general requires this kind of investigation, if only to resolve the inferences necessary for comprehension, SF would require more effort because of the semantic oddities designed to represent the science-fictional universe more or less distanced from the readers’ real reference point. This article looks at cultural and didactic approaches to the study of utopias and extraordinary journeys from the classical period to more contemporary dystopias, as well as resistant texts and the paradigm of the reader subject. A whole arsenal of tried and tested teaching methods can be used to study science fiction in the classroom.